ISOLATION, CHARACTERIZATION AND OPTIMIZATION OF AMYLASE ENZYME ACTIVITIES USING SUBMERGED FERMENTATION FROM BACILLUS SP. - RAJA HUSAIN1, NITIN VIKRAM, DEEPAK KUMAR, N. A. KHAN, KUNVAR GYANENDRA, ANJALI MALIK AKHTAR ALI, (The Bioscan, 2015)
Amylase is an important digestive enzyme used in medical studies and has several industrial and commercial applications. Due to the enormous importance of this enzyme, this study was focused on optimization of culture conditions favoring the maximum enzyme production by Bacillus sp. using submerged fermentation. The optimum conditions for enzyme production were standardized using various parameters such as incubation period, pH and temperature. The production of enzymes was found maximum (28.42 U/mL) at 120 hrs after incubation. The optimum temperature and pH of the enzyme activity were found to be 40ºC and 6 respectively. Supplementation of various carbon and nitrogen sources resulted in marginal increase in α-amylase production. Highest production was observed with starch (29.17 U/mL) and ammonium sulphate (21.90 U/mL), while amongst the minerals, magnesium sulphate (1mM) was found to induce the maximum production of amylase (37.33 U/mL).